PENERAPAN TEKNOLOGI ONLINE MONITORING KUALITAS AIR UNTUK DAS PRIORITAS DI SUNGAI CILIWUNG DAN SUNGAI CISADANE - Wahjono, Heru Dwi (Jurnal Air Indonesia, 2016)
Ciliwung and Cisadane are two main river from one of the priorities water shed set by the Indonesian government. This determination is based on one of which was the need for water resource management in Ciliwung-Casadane is already getting damaged. Ministry of Environment and Forests (KLHK) makes Ciliwung-Cisadane one of the targets of pollution control through the application of online monitoring technology for quality water. This online monitoring technology is required to obtain a continuous monitoring data to prove the pollution by industries in this watershed area. The system applied is an online and realtime water quality monitoring system based on GSM technology. In this paper will discuss the installation process, the monitoring results, and the obstacles encountered.Ã‚Â Keywords: Priorities watershed, Ciliwung-Casadane Watershed, online monitoring technology, online and realtime data.